Evolving a new idiom to express Tamil life through translations: an achievable task or impossibility? - Shriganeshan, K. (South Eastern University of Sri Lanka, 2016)
Critics have spoken of an innovative idiom to express Sri Lankan experience in English but intelligibility is a further problem faced by international readers. There are two factors that need to be considered. One is that native and traditional metaphors may not be able to express modern life. On the other hand the range of experiences and problems faced by all Sri Lankans could not be expressed by the English educated elite. Therefore achieving our goal of writing good poetry which expresses a truly Sri Lankan experience in an internationally understandable and effective medium may be made practicable through translations. They would be able to express their variety of experiences fusing modern, western and local imagery in the new idiom understandable to an international audience. Having stated the focal point, the present paper makes an attempt to look into the poems translated into English from Tamil selected from the writings of the poets living in Sri Lanka, though there are Tamil poems translated into English from India, Singapore, Malaysia and the Diaspora in Europe, Canada and Australia. The study focuses on the possibility of evolving a new idiom to express Sri Lankan Tamil life in English.
Keywords: Intelligible Idiom; Tamil Experience; Spoken Rhythm; Effective Medium